Water Birth Dan Pendamping Persalinan Dengan Lama Kala I Fase Aktif Pada Primigravida - Ika Putri Damayanti; Leni Syafitri (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Maternal Mortality Rate (MMR) in Indonesia 2007 is 228/100.000 live births. One cause of maternal death is prolonged labor caused first stage prolonged.the action accelerates the delivery process and reduce labor pain with the selection of one of them is water birth delivery method and also with the labor companion. Pekanbaru PMC hospital is the only hospital that provides water birth delivery facility on the island of Sumatra.Objective: This study was to determine the relationships of water birth and labor companion with a long active phase of the first stage in primigravida in PMC Pekanbaru Hospital in 2013.Method: Type of research study is quantitative analytic by cross sectional design. Samples totaling 105 cases according to the inclusion and exclusion criteria by using the total sampling technique. Instrument used in this study is partograf. The research data is secondary data, and analyzed using Chi-square test.Result: The results showed that maternal conventional primigravida 3.05 times more at risk than women giving birth water birth. Value of PR (95% CI) = 3.059 (1.909 to 4.901) and labor unaccompanied 2.9 times more risky than the value accompanied with PR (95% CI) = 2.965 (1,769-4,969)Keywords: Water birth, companion maternity, long Kala I, Phase active, primigravida